BECOMING HUMAN THEORY: PRACTICE IN PRE-RETIREMENT GROUP - Raquel Gvozd; Simone Domingues Garcia; Maria do Carmo Lourenço Haddad; Marli Terezinha Oliveira Vannuchi; Mara Lúcia Garanhani (Universidade Federal de Santa Maria, 2016)
Aim: To identify the principles of the Becoming Human theory in a focus group about retirement. Methods: This descriptive study with a qualitative approach was developed with five pre-retirees of a public university located in northern Paraná. There were five meetings between July and November 2012. The speeches were analyzed using the principles of the theory Becoming Human, Rosemarie Parse, which are meaning, synchronized rhythms and co-transcendence. Results: It was found that the use of the theory is possible in the study groups, such as the analyzed one. That is possible because the principles discussed will meet the idea that health and well being are influenced by situations experienced throughout life. Final Remarks: the study reveals that preretirees correspond to the principles proposed by the theory. When delivering the image of retirement, they seek knowledge and transformation in order to face this stage of life, which results in the production of a structured thinking on the subject.